Some aspects of training at English-speaking students - Kryvoruchko, I.; Tonkoglas, A.; Sykal, M.; Sivozhelezov, A. (Journal of Education, Health and Sport, 2019)
Export of educational services is a powerful factor of stimulation of economic growth and one of the conditions of overcoming an economic crisis. Many of students face the problems of communication compatibility with people of different cultures. Learning efficiency of foreign students depends on their adaptation to educational, social environment and cultural traditions. English communication is a positive factor for students of various countries. Prevention of conflicts between students because of different national features and different religion depends on professionalism of the teacher.